How a laboratory-based antimicrobial resistance (AMR) regional surveillance system can address large-scale and local AMR epidemiology: the MICRO-BIO experience - Comelli, Agnese; Zanforlini, Martina; Mazzone, Arianna; Pedroni, Palmino; De Castro, Umberto; Scarioni, Simona; D’Amelio, Anna Carole; Renisi, Giulia; Bandera, Alessandra; Gori, Andrea; Schiatti, Simone; Cereda, Danilo; et al. (Frontiers in Public Health, 2024)
Antimicrobial resistance is a significant threat to public health, with Italy experiencing substantial challenges in terms of AMR rate, surveillance system and activities to combat AMR. In response, the MICRO-BIO project was initiated as part of the National Plan to Combat Antibiotic Resistance by Region Lombardy health department. It was launched in 2018 with the aim of creating a surveillance tool by integrating data on bacterial isolates from microbiology laboratories. The participating laboratories were directly involved in reviewing and addressing discrepancies in the transmission data quality assessment. Despite the disruptions caused by COVID-19, 30 out of 33 laboratories in the Lombardy Region were successfully integrated by October 2023, with 1,201,000 microbiological data collected in the first nine months of 2023. In 2022 the analysis yielded 15,037 blood culture results from 20 labs passing validation. Data regarding the antimicrobial resistance profile of high-priority pathogens was analyzed at regional and single-hospital levels. The MICRO-BIO project represents a significant step toward strengthening AMR surveillance in a highly populated region. As a multi-disciplinary tool encompassing the fields of public health and IT (information technology), this tool has the potential to inform regional and local AMR epidemiology.